Aspek Hukum Perlindungan Konsumen - A, Arlan (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses aspects of consumer protection from the perspective of Islamic economic law as an integral part of the principles of justice and maqasid al-syari'ah, especially hifz al-mal and hifz al-nafs. This study was conducted through a qualitative approach with a literature study method on classical and contemporary literature, such as the works of Wahbah al-Zuhayli, Yusuf al-Qaradawi, and positive regulations such as Law No. 8 of 1999 concerning Consumer Protection. The results of the study show that Islam has previously regulated the principles of consumer protection through the prohibition of gharar, ghish, and the obligation of transparency in contracts. These values are in line with positive law, although national law tends not to adopt the Islamic ethical-spiritual framework as a whole. Therefore, synergy is needed between state regulations and Islamic principles in building a fair and civilized consumer protection system. This study is expected to be a conceptual contribution in building Islamic economic law that is responsive to the needs of modern society.